Fertilizers Part 1. Terminology and labelling Section 3. Specification for marking of containers (packages, drums, etc.) and labels (BSI, 1984)
Fertilizers, Agricultural chemicals, Soil improvement, Marking, Containers, Labels, Dimensions, Graphic characters, Size, Position